2016
DOI: 10.1007/s40089-015-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

A review on applications of nanotechnology in the enhanced oil recovery part A: effects of nanoparticles on interfacial tension

Abstract: Chemical enhanced oil recovery is another strong growing technology with the potential of a step change innovation, which will help to secure future oil supply by turning resources into reserves. While Substantial amount of crude oil remains in the reservoir after primary and secondary production, conventional production methods give access to on average only one-third of original oil in place, the use of surfactants and polymers allows for recovery of up to another third of this oil. Chemical flooding is of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 89 publications
2
101
0
Order By: Relevance
“…The purpose of surfactant flooding is to increase the capillary number by reducing IFT between the oil and water [1,47]. Nanofluids of 70-150 nm dissolved in aqueous solution of surfactants can result in effective oil displacement of 35% compared to using only surfactants in a homogeneous reservoir, and 17% in a heterogeneous reservoir at a temperature of 25 °C.…”
Section: Interfacial Tension (Ift) Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of surfactant flooding is to increase the capillary number by reducing IFT between the oil and water [1,47]. Nanofluids of 70-150 nm dissolved in aqueous solution of surfactants can result in effective oil displacement of 35% compared to using only surfactants in a homogeneous reservoir, and 17% in a heterogeneous reservoir at a temperature of 25 °C.…”
Section: Interfacial Tension (Ift) Reductionmentioning
confidence: 99%
“…Effect of reservoir temperature Surfactant also precipitate at high temperature, the median temperature for the surveyed surfactant project is 25.3 °C [47]. Ranka et al [64] stabilized nanoparticles at high-temperature reservoir condition.…”
Section: Effect Of Formationmentioning
confidence: 99%
“…The nanofluids usually exhibit high thermal conductivities, which are significant to the development of energy, and have been widely used in drug delivery solar cells, lipase immobilization, soil remediation, lubrication, and hydraulic fracturing of gas and oil. In addition, nanofluids have been introduced to the enhanced oil recovery (EOR) area due to their unique thermal properties and large surface area [4][5][6][7][8]. Many works have been done to study the EOR performance of nanofluids composed of different nanoparticles.…”
Section: Nanofluid Floodingmentioning
confidence: 99%
“…Recently, it was shown that the inclusion of nanoparticles into surfactant solutions affected their properties (Cheraghian and Hendraningrat, ; Khalafi et al, ; Ogolo et al, ), including viscosity (Rudyak and Krasnolutskii, ), wettability alteration effectiveness (Jha et al, , b; Nwidee et al, ), and interfacial and surface tension reduction (Dong and Johnson, ; Zargartalebi et al, ). Due to this, nanoparticles–surfactant solutions (surfactant nanofluids) have been regarded as potential formulations for improving the surfactant flooding EOR (Jha et al, , b; Joonaki and Ghanaatian, ).…”
Section: Introductionmentioning
confidence: 99%